Numerical Modeling of Tidal Current Patterns Using 3-Dimensional MOHID in Balikpapan Bay, Indonesia - Hadi Hermansyah; Nining Sari Ningsih; Nabil Nabil; Ayi Tarya; Syahruddin Syahruddin (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsThe results of the model and observation showed the similarity of the amplitude and phase formedAt the highest tide was in the position above the Sea Mean level and the current velocity was lower than when heading to the tideThere was a difference in the direction of the current when heading towards high tideStratification of the water column in both seasons tended to be classified in well-mixed watersAbstractBalikpapan Bay is significant as a link between the cities within and outside of East Kalimantan by becoming the primary path used for local transportation and distribution of produced goods. The various anthropogenic activities increased liquid wastes and debris, which flowed through channels and rivers along the bay. This study aimed to determine tidal current patterns in Balikpapan Bay and its influence on salinity and temperature distributions. This study applied a baroclinic three-dimensional (3D) hydrodynamic model, employing wind, tides, and density variations, resulting from the differences of temperature and salinity, as the model input. To simulate the tidal current flow, we applied MOHID Water Modeling System, which the tidal current patterns depicted current directions and speeds at the different tidal conditions. During the displacement toward the high tidal condition, the water mass moves northwestward entering the river body, while at the displacement toward the low tidal condition, the water mass moves southeastward, which flows toward the coast and without the bay. The current speed varies at certain tidal conditions. At the highest tidal condition, the surface elevation ranged 1.3 - 1.5 m above mean sea level; the current rate is lower compared to the displacement toward high tidal condition, which ranged from 0.01 - 0.15 m/s. At the lowest tidal condition, the surface elevation reached 1 - 1.2 m below mean sea level, and the weaker flow velocity took place (less than 0.15 m/s). The results also showed that the water mass temperature tends to be higher in the inner part of Balikpapan Bay, the Balikpapan Bay waters profile that is increasingly shallow towards the bay head also causes this area to tend to have a higher temperature. Also, areas located on the inside of the bay tend to get more freshwater input from rivers, so this area has lower salinity while the area located at the mouth of the bay tends to be of higher salinity because it gets a lot of mass input of seawater from the Makassar Strait.